Orthodontic Fixed retainers: a systematic review - Wasserman-Milhem, Isaac; Ferrer-Belloso, Karina; Gualdrón-Escalona, Jesús; Jiménez-Becerra, Nancy; Mateos-Márquez, Laura (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: the objective of this study was to evaluate the periodontal effects of fixed retainers in the long term. Methods: a search in electronic databases (PubMed, Cochrane Library, Science Direct, Embase, ProQuest, Ebsco, Biomed Central, Medline, Lilacs, and Google Scholar) and a manual search with no language restrictions. The inclusion criteria were: randomized clinical trials and meta-analysis, prospective and retrospective studies, studies in humans, clinical and radiographical studies evaluating the periodontium, performed during the 1987-2014 period, up to 10 years of follow-up. Four authors extracted data from the selected studies independently. Results: after applying the inclusion criteria, we selected 4 studies in which a total of 405 patients were evaluated. All the studies were longitudinal and retrospective. There was a greater prevalence of gingival recessions, especially in mandibular incisors, which are more vulnerable. There were no significant changes in terms of alveolar bone index or calculus index. The survival rate of fixed retainers was 50% or higher. Due to the heterogeneity of the selected studies, including difference in study population, differences in methods to assess the intervention, and follow-up periods, it was impossible to quantify the variables to perform a meta-analysis. Conclusions: the selected studies had a middle level of evidence. The greatest gingival recessions occurred with the use of fixed retainers in a long time; however, there is no alteration of the alveolar bone level. The studies recommend encouraging patients to maintain good oral hygiene. The findings of this review should be cautiously taken due to the resulting level of evidence, and the general recommendation for clinicians is that, in the long run, these retainers appear to be safe to maintain the alignment of mandibular incisors, although more studies with greater scientific rigor are required. There were no conflicts of interest and this study did not have any kind of financial support.